Changes in Immunological Parameters in Patients Treated Using Direct and Indirect Restorations of the Hard Tissues of the Anterior Teeth in Combination with an Antioxidant (Indian Journal of Forensic Medicine & Toxicology, 2020)
The problem of aesthetic restoration of the hard tissue defects in the anterior teeth and the choice of materialsfor quality restorations, which can include direct composite or indirect ceramic restoration, in particularceramic veneers, is currently extremely important in clinical dental orthopedics. Currently used compositeand ceramic materials are known to have different effects on the conditions of the marginal periodontiumand the local immunity in the oral cavity. Therefore, we propose a new approach to treatment, which isthe use of indirect ceramic restorations in combination with an antioxidant. The purpose of this article isto increase the effectiveness of treatment in patients with defects in anterior teeth using indirect ceramicrestorations with antioxidants. To study the intensity of immune reactivity in patients with existing defectsof the coronal part of the anterior teeth, we analyzed the levels of lysozyme and sIgA in the oral fluid. Theresults of the studies confirm the advantages of indirect ceramic restorations over direct composite ones inthe treatment of hard tissue defects in the anterior teeth, taking into account the levels of immunologicalreactivity and using an antioxidant drug Resverasin.
Keywords: peroxide compounds, bactericidal effects, caries, tooth tissues.